Potensi Ekowisata di Kawasan Mangrove Dusun Tuing Kabupaten Bangka - Farhaby, Arthur Muhammad; Supratman, Okto; Okto Supratman (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Â Tuing is a remoteÂ location in the Riau Silip District, Bangka Regency. Tuing has potential of marine fishery resources as well as tourism development potential to be developed in Bangka Regency. In addition to the resource potential of natural resources,moreover it is also rich in tin because almost all seas from 0-4 nautical miles have been issued by marine mining permits. This study aims to determine the suitability of mangrove land in Tuing to be developed as a tourist location. Data taken includes mangrove tourism suitability data, such as vegetation and environmental parameters. Based on the results of the analysis of ecotourism location suitability in the eight stations, stations 1,3,5,6 and 7 have inter-values of 86-96% or in the S1 category: with grades 80-100% (Very Appropriate), while the index values are different at stations 2 and 8 have a value of 52-69% in the S2 category: with a value of 60-80% (quite appropriate). Ecologically, there are 4 mangrove species, Soneratia alba, Rhizophora apiculata, Avicennia sp., Rhizophora mucronata. Accordingly, recommendations for development strategies the need for regulation of mining activities around the Tuing mangrove forest area, training for tourism-related businesses with local resources and ordinarily need more funding to provide support facilities and infrastructure.